Fibrous cellulose, fibrous cellulose composite resin, and method for producing fibrous cellulose

By introducing carbamate groups into fibrous cellulose with specific properties, the method enhances dispersibility and resin compatibility, addressing the dispersibility issues and improving the reinforcing effect and strength of fibrous cellulose composites.

JP2025003523AActive Publication Date: 2025-01-09DAIO PAPER CORP

Patent Information

Application Number
JP2024182474
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-09
Estimated Expiration
2040-03-26

AI Technical Summary

Technical Problem

Existing fibrous cellulose composites face issues with resin dispersibility due to hydrophilic fibers and hydrophobic resins, leading to insufficient reinforcing effects and resin breakdown at non-uniform locations.

Method used

Introduce carbamate groups into fibrous cellulose with specific properties, including an average fiber width of 0.1 μm or more, a substitution rate of 1.0 mmol/g or more, and a fine rate of 30% or more, to enhance dispersibility and resin compatibility.

Benefits of technology

The method produces fibrous cellulose with improved resin reinforcing effects and high strength, reducing resin heterogeneity and breakdown, resulting in a more uniform composite.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025003523000001
    Figure 2025003523000001
  • Figure 2025003523000002
    Figure 2025003523000002
  • Figure 2025003523000003
    Figure 2025003523000003
Patent Text Reader

Abstract

To provide a fibrous cellulose having high reinforcing effect of a resin, a fibrous cellulose composite resin having high intensity, and a method for producing the fibrous cellulose having the high reinforcing effect of the resin.SOLUTION: A fibrous cellulose has an average fiber width of 0.1 μm or more, has some or all of hydroxyl groups substituted with carbamate groups, has a carbamate group substitution rate of 1.0 mmol / g or more, and has a fine rate of 30% or more. The fibrous cellulose composite resin comprises fibrous cellulose and a resin, the fibrous cellulose being the aforementioned fibrous cellulose. Moreover, when producing the fibrous cellulose, a cellulose raw material and urea or the like are heat-treated and some or all of the hydroxyl groups in the cellulose raw material are substituted by the carbamate groups, the fibers are separated until the average fiber width is 0.1 μm or more, the heat treatment is performed such that the carbamate group substitution rate reaches 1.0 mmol / g or more, and the fibers are separated until the fine rate is 30% or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fibrous cellulose, a fibrous cellulose composite resin, and a method for producing fibrous cellulose. [Background technology]

[0002] In recent years, fine fibers such as cellulose nanofibers and microfiber cellulose (microfibrillated cellulose) have been in the spotlight for use as reinforcing materials for resins. However, since fine fibers are hydrophilic while resins are hydrophobic, there is a problem with the dispersibility of the fine fibers when using the fine fibers as reinforcing materials for resins. Therefore, the present inventors have proposed substituting the hydroxyl groups of the fine fibers with carbamate groups (see Patent Document 1). According to this proposal, the dispersibility of the fine fibers is improved, and the reinforcing effect of the resin is improved. However, even now, there is a demand for further improvement in the reinforcing effect, and various researches are being conducted. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-1876 A Summary of the Invention [Problem to be solved by the invention]

[0004] A main problem to be solved by the invention is to provide fibrous cellulose having a high reinforcing effect for resins, a fibrous cellulose composite resin having high strength, and a method for producing fibrous cellulose having a high reinforcing effect for resins. [Means for solving the problem]

[0005] In the past developments, for example, in the developments of the above patent documents, the main focus was on the modification of fine fibers, and among the many existing modification methods such as esterification, etherification, amidation, and sulfidation, the introduction of carbamate groups (carbamation) was found to be superior. In contrast, the present invention does not focus on the introduction of carbamate groups, but rather, in the course of conducting various tests on the premise of the introduction of carbamate groups, the reinforcing effect of the resin was analyzed in detail, and it was found and conceived that the above-mentioned problems could be solved by pursuing the physical properties of the fine fibers. More specifically, one of the causes of the insufficient reinforcing effect of the resin is the destruction of the resin, and this destruction of the resin occurs from the heterogeneous parts present in the resin. In order to eliminate the heterogeneity of the resin, one rational solution is to aim to improve the dispersibility of the fine fibers, and in this respect, the introduction of carbamate groups has made a great advance. However, it has also been found that the more heterogeneous the fibers are contained, the more easily the destruction of the resin progresses, and the means that have been conceived through such knowledge are as follows.

[0006] (Means described in claim 1) The average fiber width is 0.1 μm or more, and some or all of the hydroxyl groups are replaced with carbamate groups represented by the "-CO-NH2" group. The substitution rate of the carbamate group is 1.0 mmol / g or more, The fineness ratio is 30% or more. Crystallinity is 50% or more That is, Fibrous cellulose characterized by:

[0007] (Means described in claim 2) Crystallinity is 95% or less That is, 2. The fibrous cellulose of claim 1.

[0008] (Means described in claim 3) The fine ratio of the raw cellulose material is 1% or more. 3. Fibrous cellulose according to claim 1 or 2.

[0009] (Means described in claim 4) Contains fibrous cellulose and resin, The fibrous cellulose is The average fiber width is 0.1 μm or more, and some or all of the hydroxyl groups are replaced with carbamate groups represented by the "-CO-NH2" group. The substitution rate of the carbamate group is 1.0 mmol / g or more, The fineness ratio is 30% or more. Crystallinity is 50% or more That is, A fibrous cellulose composite resin characterized by:

[0010] (Means described in claim 5) The standard deviation of the flexural modulus measured in accordance with JIS K 7171 is 30 MPa or less. The fibrous cellulose composite resin according to claim 4.

[0011] (Means described in claim 6) A process for heat-treating a cellulose raw material and at least one of urea and a urea derivative to replace some or all of the hydroxyl groups of the cellulose raw material with carbamate groups represented by "-CO-NH2" groups; The cellulose raw material is defibrated to an average fiber width of 0.1 μm or more. The heat treatment is carried out so that the substitution rate of the carbamate group is 1.0 mmol / g or more, The defibration is carried out until the fineness ratio reaches 30% or more. Crystallinity of 50% or more Let us say, 5. A method for producing fibrous cellulose comprising the steps of: Effect of the Invention

[0012] According to the invention, there are provided fibrous cellulose having a high reinforcing effect for resins, a fibrous cellulose composite resin having high strength, and a method for producing fibrous cellulose having a high reinforcing effect for resins. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Next, an embodiment of the present invention will be described. Note that the embodiment is an example of the present invention. The scope of the present invention is not limited to the scope of the embodiment.

[0014] The fibrous cellulose of this embodiment (hereinafter also referred to as "cellulose fiber") has an average fiber width (diameter) of 0.1 μm or more, and some or all of the hydroxyl groups (-OH groups) are substituted with carbamate groups. In addition, the substitution rate of the carbamate groups is 1.0 mmol / g or more, and the fineness ratio is 30% or more. Furthermore, a fibrous cellulose composite resin is constituted by containing this fibrous cellulose and a resin. Furthermore, the method for producing fibrous cellulose includes a step of heat-treating a cellulose raw material and urea or a derivative of urea to substitute some or all of the hydroxyl groups of the cellulose raw material with carbamate groups, and a step of defibrating the cellulose raw material to a range in which the average fiber width is 0.1 μm or more to obtain microfibrous cellulose. The heat treatment is performed so that the substitution rate of the carbamate groups is 1.0 mmol / g or more, and the defibration is performed until the fineness ratio is 30% or more. The process will be described in detail below.

[0015] (fibrous cellulose) The fibrous cellulose composite resin of the present embodiment contains fibrous cellulose (hereinafter also referred to as "cellulose fiber"), a resin, and preferably an acid-modified resin. When the acid-modified resin is contained, a part or all of the carbamate groups are ionically bonded to the acid groups of the acid-modified resin.

[0016] In this embodiment, the fibrous cellulose, which is a fine fiber, is a microfiber cellulose (microfibrillated cellulose) having an average fiber diameter of 0.1 μm or more. The microfiber cellulose significantly improves the reinforcing effect of the resin. In addition, microfiber cellulose is easier to modify with a carbamate group (carbamation) than cellulose nanofiber, which is also a fine fiber. However, it is more preferable to carbamate the cellulose raw material before micronization, and in this case, microfiber cellulose and cellulose nanofiber are equivalent.

[0017] In this embodiment, microfiber cellulose means a fiber having a larger average fiber width than cellulose nanofiber. Specifically, the average fiber diameter is, for example, 0.1 to 20 μm, preferably 0.2 to 19 μm, and more preferably more than 0.5 to 18 μm. When the average fiber diameter of microfiber cellulose is less than 0.1 μm, it becomes the same as cellulose nanofiber, and there is a possibility that the effect of improving the strength (particularly bending modulus) of the resin cannot be sufficiently obtained. In addition, the defibration time becomes longer, and a large amount of energy is required. Furthermore, the dehydration of the cellulose fiber slurry is deteriorated. When the dehydration is deteriorated, a large amount of energy is required for drying, and when a large amount of energy is applied for drying, the microfiber cellulose is thermally deteriorated, and the strength may be reduced. On the other hand, when the average fiber diameter of microfiber cellulose exceeds 20 μm, it becomes the same as pulp, and there is a possibility that the reinforcing effect becomes insufficient.

[0018] Microfiber cellulose can be obtained by defibrating (refining) a cellulose raw material (hereinafter also referred to as "raw pulp"). As the raw pulp, one or more types can be selected from wood pulp made from broadleaf trees, coniferous trees, etc., non-wood pulp made from straw, bagasse, cotton, hemp, bast fiber, etc., and waste paper pulp (DIP) made from recycled waste paper, broke paper, etc. The above various raw materials may be in the form of a pulverized material (powdered material), for example, called cellulose-based powder.

[0019] However, in order to prevent impurities from being mixed in as much as possible, it is preferable to use wood pulp as the raw material pulp. As the wood pulp, for example, one or more types may be selected from chemical pulps such as hardwood kraft pulp (LKP) and softwood kraft pulp (NKP), and mechanical pulp (TMP), etc.

[0020] The hardwood kraft pulp may be bleached hardwood kraft pulp, unbleached hardwood kraft pulp, or semi-bleached hardwood kraft pulp. Similarly, the softwood kraft pulp may be bleached softwood kraft pulp, unbleached softwood kraft pulp, or semi-bleached softwood kraft pulp.

[0021] As the mechanical pulp, for example, one or more types can be selected and used from stone ground pulp (SGP), pressed stone ground pulp (PGW), refiner ground pulp (RGP), chemi-ground pulp (CGP), thermo-ground pulp (TGP), ground pulp (GP), thermo-mechanical pulp (TMP), chemi-thermomechanical pulp (CTMP), refiner mechanical pulp (RMP), bleached thermo-mechanical pulp (BTMP), etc.

[0022] The raw pulp can be pretreated by a chemical method prior to defibration. Examples of pretreatment by a chemical method include hydrolysis of polysaccharides by acid (acid treatment), hydrolysis of polysaccharides by enzymes (enzyme treatment), swelling of polysaccharides by alkali (alkali treatment), oxidation of polysaccharides by an oxidizing agent (oxidation treatment), reduction of polysaccharides by a reducing agent (reduction treatment), and the like. However, as the pretreatment by a chemical method, it is preferable to carry out an enzyme treatment, and it is more preferable to additionally carry out one or more treatments selected from an acid treatment, an alkali treatment, and an oxidation treatment. The enzyme treatment will be described in detail below.

[0023] As the enzyme used in the enzymatic treatment, it is preferable to use at least one of cellulase enzymes and hemicellulase enzymes, and more preferably to use both in combination. The use of these enzymes makes it easier to defibrate the cellulose raw material. Note that cellulase enzymes cause the decomposition of cellulose in the presence of water. Also, hemicellulase enzymes cause the decomposition of hemicellulose in the presence of water.

[0024] Examples of cellulase enzymes that can be used include enzymes produced by the genera Trichoderma (filamentous fungi), Acremonium (filamentous fungi), Aspergillus (filamentous fungi), Phanerochaete (basidiomycetes), Trametes (basidiomycetes), Humicola (filamentous fungi), Bacillus (bacteria), Schizophyllum (basidiomycetes), Streptomyces (bacteria), and Pseudomonas (bacteria). These cellulase enzymes are available as reagents or commercially available products. Examples of commercially available products include Cellulose T2 (manufactured by HPI), Meicerase (manufactured by Meiji Seika Kaisha), Novozym 188 (manufactured by Novozym), Multifect CX10L (manufactured by Genencor), and cellulase enzyme GC220 (manufactured by Genencor).

[0025] As the cellulase enzyme, either EG (endoglucanase) or CBH (cellobiohydrolase) can be used. EG and CBH can be used alone or in combination. They can also be used in combination with a hemicellulase enzyme.

[0026] Examples of hemicellulase enzymes that can be used include xylanase, which is an enzyme that breaks down xylan, mannase, which is an enzyme that breaks down mannan, and arabanase, which is an enzyme that breaks down araban. Also, pectinase, which is an enzyme that breaks down pectin, can be used.

[0027] Hemicellulose is a polysaccharide, excluding pectins, found between cellulose microfibrils in plant cell walls. Hemicellulose is diverse and differs depending on the type of wood and between the layers of the cell wall. In the secondary walls of softwoods, glucomannan is the main component, while in the secondary walls of hardwoods, 4-O-methylglucuronoxylan is the main component. Therefore, when obtaining fine fibers from softwood bleached kraft pulp (NBKP), it is preferable to use mannase. Also, when obtaining fine fibers from hardwood bleached kraft pulp (LBKP), it is preferable to use xylanase.

[0028] The amount of enzyme added to the cellulose raw material is determined by, for example, the type of enzyme, the type of wood used as the raw material (coniferous or broadleaf), the type of mechanical pulp, etc. However, the amount of enzyme added to the cellulose raw material is preferably 0.1 to 3 mass%, more preferably 0.3 to 2.5 mass%, and particularly preferably 0.5 to 2 mass%. If the amount of enzyme added is less than 0.1 mass%, the effect of adding the enzyme may not be sufficiently obtained. On the other hand, if the amount of enzyme added is more than 3 mass%, cellulose may be saccharified, and the yield of fine fibers may decrease. There is also a problem that the effect improvement corresponding to the increase in the amount added may not be observed.

[0029] When a cellulase enzyme is used as the enzyme, the pH during the enzyme treatment is preferably in the weak acidic range (pH = 3.0 to 6.9) from the viewpoint of the reactivity of the enzyme reaction, whereas when a hemicellulase enzyme is used as the enzyme, the pH during the enzyme treatment is preferably in the weak alkaline range (pH = 7.1 to 10.0).

[0030] The temperature during the enzyme treatment is preferably 30 to 70° C., more preferably 35 to 65° C., and particularly preferably 40 to 60° C., regardless of whether a cellulase enzyme or a hemicellulase enzyme is used as the enzyme. If the temperature during the enzyme treatment is 30° C. or higher, the enzyme activity is less likely to decrease, and it is possible to prevent the treatment time from being prolonged. On the other hand, if the temperature during the enzyme treatment is 70° C. or lower, it is possible to prevent the enzyme from being deactivated.

[0031] The time for the enzyme treatment depends on, for example, the type of enzyme, the temperature of the enzyme treatment, the pH during the enzyme treatment, etc. However, the time for the enzyme treatment is generally 0.5 to 24 hours.

[0032] After the enzyme treatment, it is preferable to inactivate the enzyme. Examples of methods for inactivating the enzyme include a method of adding an alkaline aqueous solution (preferably pH 10 or higher, more preferably pH 11 or higher) and a method of adding hot water at 80 to 100°C.

[0033] Next, the method of alkali treatment will be described. When the pulp is treated with alkali prior to defibration, some of the hydroxyl groups in the hemicellulose and cellulose contained in the pulp are dissociated and the molecules are anionized, weakening intra- and intermolecular hydrogen bonds and promoting the dispersion of the cellulose raw material during defibration.

[0034] Examples of the alkali used in the alkali treatment include organic alkalis such as sodium hydroxide, lithium hydroxide, potassium hydroxide, an aqueous ammonia solution, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, and benzyltrimethylammonium hydroxide. However, from the viewpoint of production costs, it is preferable to use sodium hydroxide.

[0035] By subjecting the microfibrous cellulose to an enzyme treatment, acid treatment, or oxidation treatment prior to defibration, the water retention of the microfibrous cellulose can be reduced, the crystallinity can be increased, and the homogeneity can be improved. In this regard, when the water retention of the microfibrous cellulose is low, it becomes easier to dehydrate, and the dewaterability of the cellulose fiber slurry is improved.

[0036] When raw pulp is treated with enzymes, acids, or oxidation, the hemicellulose and amorphous regions of cellulose contained in the pulp are decomposed. As a result, the energy required for defibration can be reduced, and the uniformity and dispersibility of the cellulose fibers can be improved. However, since pretreatment reduces the aspect ratio of microfiber cellulose, excessive pretreatment is preferably avoided when using it as a reinforcing material for resins.

[0037] The raw material pulp can be defibrated by beating the raw material pulp using, for example, a homogenizer such as a beater, a high-pressure homogenizer, or a high-pressure homogenizer, a stone mill-type friction machine such as a grinder or a grinding machine, a single-shaft kneader, a multi-shaft kneader, a kneader refiner, a jet mill, etc. However, it is preferable to use a refiner or a jet mill.

[0038] The average fiber length (average length of single fibers) of the microfiber cellulose is preferably 0.10 to 2.00 mm, more preferably 0.12 to 1.50 mm, and particularly preferably 0.15 to 1.00. If the average fiber length is less than 0.10 mm, a three-dimensional network cannot be formed between the fibers, and the bending modulus of the composite resin may decrease, and even if the fine ratio is set to 35% or more to improve the homogeneity, the reinforcing effect may not be improved. On the other hand, if the average fiber length exceeds 2.00 mm, the reinforcing effect may be insufficient because the length is the same as that of the raw pulp.

[0039] The average fiber length of the cellulose raw material that is the raw material for the microfiber cellulose is preferably 0.50 to 5.00 mm, more preferably 1.00 to 3.00 mm, and particularly preferably 1.50 to 2.50. If the average fiber length of the cellulose raw material is less than 0.50 mm, the reinforcing effect of the resin may not be sufficiently obtained when the fiberization process is performed. On the other hand, if the average fiber length exceeds 5.00 mm, there is a risk of being disadvantageous in terms of production costs during fiberization.

[0040] The average fiber length of the microfibrous cellulose can be adjusted as desired by, for example, selecting the raw pulp, pre-treating, defibrating, and the like.

[0041] The fine ratio of the microfiber cellulose is preferably 30% or more, more preferably 35 to 99%, and particularly preferably 40 to 95%. If the fine ratio is 30% or more, the proportion of homogeneous fibers is high, and the destruction of the composite resin is less likely to progress. However, if the fine ratio exceeds 99%, the bending modulus may be insufficient.

[0042] The above is the fineness ratio of the microfiber cellulose, but it is more preferable to set the fineness ratio of the cellulose raw material that is the raw material for the microfiber cellulose within a specified range. Specifically, the fineness ratio of the cellulose raw material that is the raw material for the microfiber cellulose is preferably 1% or more, more preferably 3 to 20%, and particularly preferably 5 to 18%. If the fineness ratio of the cellulose raw material before defibration is within the above range, it is considered that even if the microfiber cellulose is defibrated to have a fineness ratio of 30% or more, the damage to the fibers is small and the reinforcing effect of the resin is improved.

[0043] The fine ratio can be adjusted by pretreatment such as enzyme treatment. However, especially when enzyme treatment is performed, the fiber itself may become tattered, and the reinforcing effect of the resin may decrease. Therefore, from this viewpoint, the amount of enzyme added is preferably 2% by mass or less, more preferably 1% by mass or less, and particularly preferably 0.5% by mass or less. Also, not performing enzyme treatment (addition amount 0% by mass) is also an option.

[0044] In this embodiment, the "fine ratio" refers to the mass ratio of pulp fibers having a fiber length of 0.2 mm or less.

[0045] The aspect ratio of the microfibrous cellulose is preferably 2 to 15,000, more preferably 10 to 10,000. If the aspect ratio is less than 2, a three-dimensional network cannot be sufficiently constructed, and therefore even if the average fiber length is 0.10 mm or more, the reinforcing effect may be insufficient. On the other hand, if the aspect ratio exceeds 15,000, the entanglement of the microfibrous cellulose becomes high, and dispersion in the resin may be insufficient.

[0046] The fibrillation rate of the microfibrous cellulose is preferably 1.0 to 30.0%, more preferably 1.5 to 20.0%, and particularly preferably 2.0 to 15.0%. If the fibrillation rate exceeds 30.0%, the contact area with water becomes too large, so that dehydration may become difficult even if the cellulose is defibrated to an average fiber width of 0.1 μm or more. On the other hand, if the fibrillation rate is less than 1.0%, there may be few hydrogen bonds between fibrils, and it may not be possible to form a strong three-dimensional network.

[0047] In this embodiment, the fibrillation rate refers to a value obtained by disintegrating cellulose fibers in accordance with JIS-P-8220:2012 "Pulp Disintegration Method" and measuring the resulting disintegrated pulp using FiberLab. (Kajaani).

[0048] The crystallinity of the microfiber cellulose is preferably 50% or more, more preferably 55% or more, and particularly preferably 60% or more. If the crystallinity is less than 50%, the mixability with pulp and cellulose nanofibers is improved, but the strength of the fiber itself is reduced, so that the strength of the resin may not be improved. On the other hand, the crystallinity of the microfiber cellulose is preferably 95% or less, more preferably 90% or less, and particularly preferably 85% or less. If the crystallinity is more than 95%, the proportion of strong hydrogen bonds in the molecule increases, the fiber itself becomes rigid, and dispersibility becomes poor.

[0049] The crystallinity of the microfibrous cellulose can be adjusted as desired, for example, by selecting the raw pulp, pre-treating it, and refining it.

[0050] The pulp viscosity of the microfiber cellulose is preferably 2 cps or more, more preferably 4 cps or more. If the pulp viscosity of the microfiber cellulose is less than 2 cps, it may be difficult to suppress the aggregation of the microfiber cellulose.

[0051] The freeness of the microfibrous cellulose is preferably 500 ml or less, more preferably 300 ml or less, and particularly preferably 100 ml or less. If the freeness of the microfibrous cellulose exceeds 500 ml, the average fiber diameter of the microfibrous cellulose exceeds 20 μm, and the strength improving effect of the resin may not be sufficiently obtained.

[0052] The zeta potential of the microfibrous cellulose is preferably -150 to 20 mV, more preferably -100 to 0 mV, and particularly preferably -80 to -10 mV. If the zeta potential is less than -150 mV, the compatibility with the resin may be significantly reduced, resulting in insufficient reinforcing effect. On the other hand, if the zeta potential is more than 20 mV, the dispersion stability may be reduced.

[0053] The water retention of the microfibrous cellulose is preferably 80 to 400%, more preferably 90 to 350%, and particularly preferably 100 to 300%. If the water retention is less than 80%, the reinforcing effect may be insufficient because the water retention is no different from that of the raw material pulp. On the other hand, if the water retention exceeds 400%, the dewatering property tends to be poor and the microfibrous cellulose is easily aggregated. In this respect, the water retention of the microfibrous cellulose can be further reduced by substituting the hydroxyl group of the fiber with a carbamate group, and the dewatering property and drying property can be improved.

[0054] The water retention of the microfiber cellulose can be adjusted as desired by, for example, selecting the raw pulp, pre-treating it, defibrating it, and the like.

[0055] The microfiber cellulose has a carbamate group. There is no particular limitation on how the microfiber cellulose has the carbamate group. For example, the microfiber cellulose may have the carbamate group by carbamateizing a cellulose raw material, or the microfiber cellulose (a finely divided cellulose raw material) may have the carbamate group by carbamateizing.

[0056] Incidentally, having a carbamate group means that a carbamate group (an ester of carbamic acid) is introduced into the fibrous cellulose. The carbamate group is a group represented by -O-CO-NH-, for example, a group represented by -O-CO-NH2, -O-CONHR, -O-CO-NR2, etc. In other words, the carbamate group can be represented by the following structural formula (1).

[0057] [ka]

[0058] Here, R is independently at least one of a saturated linear hydrocarbon group, a saturated branched hydrocarbon group, a saturated cyclic hydrocarbon group, an unsaturated linear hydrocarbon group, an unsaturated branched hydrocarbon group, an aromatic group, and a derivative thereof.

[0059] Examples of the saturated linear hydrocarbon group include linear alkyl groups having 1 to 10 carbon atoms, such as a methyl group, an ethyl group, and a propyl group.

[0060] Examples of the saturated branched hydrocarbon group include branched alkyl groups having 3 to 10 carbon atoms, such as an isopropyl group, a sec-butyl group, an isobutyl group, and a tert-butyl group.

[0061] Examples of the saturated cyclic hydrocarbon group include cycloalkyl groups such as a cyclopentyl group, a cyclohexyl group, and a norbornyl group.

[0062] Examples of the unsaturated linear hydrocarbon group include linear alkenyl groups having 2 to 10 carbon atoms, such as ethenyl, propen-1-yl, and propen-3-yl, and linear alkynyl groups having 2 to 10 carbon atoms, such as ethynyl, propyn-1-yl, and propyn-3-yl.

[0063] Examples of the unsaturated branched hydrocarbon group include branched alkenyl groups having 3 to 10 carbon atoms, such as a propen-2-yl group, a buten-2-yl group, and a buten-3-yl group, and branched alkynyl groups having 4 to 10 carbon atoms, such as a butyn-3-yl group.

[0064] Examples of the aromatic group include a phenyl group, a tolyl group, a xylyl group, and a naphthyl group.

[0065] Examples of derivative groups include groups in which one or more hydrogen atoms in the above-mentioned saturated linear hydrocarbon groups, saturated branched hydrocarbon groups, saturated cyclic hydrocarbon groups, unsaturated linear hydrocarbon groups, unsaturated branched hydrocarbon groups, and aromatic groups are substituted with substituents (e.g., hydroxy groups, carboxy groups, halogen atoms, etc.).

[0066] In microfiber cellulose having a carbamate group (introduced with a carbamate group), some or all of the highly polar hydroxyl groups are substituted with carbamate groups having relatively low polarity. Therefore, microfiber cellulose having a carbamate group has low hydrophilicity and high affinity with resins having low polarity. As a result, microfiber cellulose having a carbamate group has excellent uniform dispersion with resins. In addition, a slurry of microfiber cellulose having a carbamate group has low viscosity and good handling properties.

[0067] The substitution rate of the carbamate group for the hydroxyl group of the microfiber cellulose is preferably 1.0 to 5.0 mmol / g, more preferably 1.2 to 3.0 mmol / g, and particularly preferably 1.5 to 2.0 mmol / g. When the substitution rate is 1.0 mmol / g or more, the effect of introducing the carbamate group, particularly the effect of improving the bending modulus of the resin, is reliably achieved. On the other hand, when the substitution rate exceeds 5.0 mmol / g, the cellulose fiber cannot maintain the shape of the fiber, and the reinforcing effect of the resin may not be sufficiently obtained. In addition, when the substitution rate of the carbamate group exceeds 2.0 mmol / g, the average fiber length of the pulp becomes short when the raw material pulp is carbamateized, and as a result, the average fiber length of the microfiber cellulose becomes less than 0.1 mm, and there is a risk that the resin reinforcing effect may not be sufficiently obtained.

[0068] In this embodiment, the carbamate group substitution rate (mmol / g) refers to the amount of carbamate groups contained in 1 g of cellulose raw material having carbamate groups. The carbamate group substitution rate is calculated by measuring the N atoms present in the carbamate-treated pulp by the Kjeldahl method and calculating the carbamate rate per unit weight. Cellulose is a polymer with anhydroglucose as a structural unit, and has three hydroxyl groups per structural unit.

[0069] <Carbamate formation> Regarding the introduction of carbamate groups (carbamation) into microfiber cellulose (when carbamate is performed before defibration, it is the cellulose raw material. Hereinafter, the same is also referred to as "microfiber cellulose, etc."), there are a method of carbamate-ifying the cellulose raw material and then refining it, as described above, and a method of refining the cellulose raw material and then carbamate-ifying it. In this regard, in this specification, defibration of the cellulose raw material is explained first, and then carbamate-ification (modification) is explained. However, either defibration or carbamate-ification can be performed first. However, it is preferable to perform carbamate-ification first and then defibration. This is because the cellulose raw material before defibration has a high dehydration efficiency, and the cellulose raw material is in a state that is easily defibrated by the heating associated with carbamate-ification.

[0070] The process of carbamate-converting microfibrous cellulose or the like can be mainly divided into, for example, a mixing process, a removal process, and a heat treatment. The mixing process and the removal process can be collectively referred to as a conditioning process for preparing a mixture to be subjected to a heat treatment.

[0071] In the mixing process, microfiber cellulose or the like (which may be a cellulose raw material as described above, the same applies below) and urea or a derivative of urea (hereinafter simply referred to as "urea, etc.") are mixed in a dispersion medium.

[0072] Examples of urea and urea derivatives that can be used include urea, thiourea, biuret, phenylurea, benzylurea, dimethylurea, diethylurea, tetramethylurea, and compounds in which the hydrogen atoms of urea are substituted with alkyl groups. These urea and urea derivatives can be used alone or in combination. However, it is preferable to use urea.

[0073] The lower limit of the mixture mass ratio of urea etc. to microfiber cellulose etc. (urea etc. / microfiber cellulose etc.) is preferably 10 / 100, more preferably 20 / 100. On the other hand, the upper limit is preferably 300 / 100, more preferably 200 / 100. By making the mixture mass ratio 10 / 100 or more, the efficiency of carbamate formation is improved. On the other hand, even if the mixture mass ratio exceeds 300 / 100, the carbamate formation reaches a plateau.

[0074] The dispersion medium is usually water, although other dispersion media such as alcohols, ethers, and mixtures of water with other dispersion media may also be used.

[0075] In the mixing treatment, for example, microfibrous cellulose, etc. and urea, etc. may be added to water, microfibrous cellulose, etc. may be added to an aqueous solution of urea, etc., or urea, etc. may be added to a slurry containing microfibrous cellulose, etc. In order to mix uniformly, stirring may be performed after addition. Furthermore, the dispersion containing microfibrous cellulose, etc. and urea, etc. may contain other components.

[0076] In the removal treatment, the dispersion medium is removed from the dispersion liquid containing the microfibrous cellulose etc. and urea etc. obtained in the mixing treatment. By removing the dispersion medium, the urea etc. can be reacted efficiently in the subsequent heat treatment.

[0077] The dispersion medium is preferably removed by volatilizing it by heating, which makes it possible to efficiently remove only the dispersion medium while leaving behind the components such as urea.

[0078] When the dispersion medium is water, the lower limit of the heating temperature in the removal treatment is preferably 50°C, more preferably 70°C, and particularly preferably 90°C. By setting the heating temperature at 50°C or higher, the dispersion medium can be efficiently volatilized (removed). On the other hand, the upper limit of the heating temperature is preferably 120°C, more preferably 100°C. If the heating temperature exceeds 120°C, the dispersion medium and urea may react, and the urea may independently decompose.

[0079] The heating time in the removal treatment can be appropriately adjusted depending on the solid content concentration of the dispersion liquid, etc. Specifically, it is, for example, 6 to 24 hours.

[0080] In the heat treatment following the removal treatment, a mixture of the microfiber cellulose and urea is heat-treated. In this heat treatment, some or all of the hydroxyl groups of the microfiber cellulose react with urea and are replaced with carbamate groups. More specifically, when urea is heated, it is decomposed into isocyanic acid and ammonia as shown in the following reaction formula (1). Isocyanic acid is very reactive, and for example, carbamate groups are formed on the hydroxyl groups of cellulose as shown in the following reaction formula (2). NH2-CO-NH2→ HN=C=O + NH3…(1) Cell-OH + HN=C=O → Cell-CO-NH2…(2) The lower limit of the heating temperature in the heat treatment is preferably 120°C, more preferably 130°C, particularly preferably the melting point of urea (about 134°C) or higher, even more preferably 140°C, and most preferably 150°C. By setting the heating temperature at 120°C or higher, carbamate formation is efficiently carried out. The upper limit of the heating temperature is preferably 200°C, more preferably 180°C, and particularly preferably 170°C. If the heating temperature exceeds 200°C, the microfiber cellulose and the like may decompose, resulting in insufficient reinforcing effect.

[0081] The lower limit of the heating time in the heat treatment is preferably 1 minute, more preferably 5 minutes, particularly preferably 30 minutes, even more preferably 1 hour, and most preferably 2 hours. By setting the heating time to 1 minute or more, the carbamate reaction can be carried out reliably. On the other hand, the upper limit of the heating time is preferably 15 hours, more preferably 10 hours. If the heating time exceeds 15 hours, it is not economical, and carbamate reaction can be sufficiently carried out in 15 hours.

[0082] However, prolonged heating time leads to deterioration of cellulose fibers. Therefore, the pH conditions in the heat treatment are important. The pH is preferably 9 or more, more preferably 9 to 13, and particularly preferably 10 to 12, which is an alkaline condition. As a second best option, the pH is 7 or less, preferably 3 to 7, and particularly preferably 4 to 7, which is an acidic or neutral condition. Under neutral conditions of pH 7 to 8, the average fiber length of the cellulose fibers is shortened, and the reinforcing effect of the resin may be inferior. On the other hand, under alkaline conditions of pH 9 or more, the reactivity of the cellulose fibers is increased, the reaction with urea, etc. is promoted, and the carbamate reaction occurs efficiently, so that the average fiber length of the cellulose fibers can be sufficiently secured. On the other hand, under acidic conditions of pH 7 or less, the reaction of decomposing urea, etc. into isocyanic acid and ammonia proceeds, the reaction with cellulose fibers is promoted, and the carbamate reaction occurs efficiently, so that the average fiber length of the cellulose fibers can be sufficiently secured. However, if possible, it is preferable to perform the heat treatment under alkaline conditions. This is because acidic conditions may cause acid hydrolysis of cellulose to proceed.

[0083] The pH can be adjusted by adding an acidic compound (eg, acetic acid, citric acid, etc.) or an alkaline compound (eg, sodium hydroxide, calcium hydroxide, etc.) to the mixture.

[0084] As a heating device in the heat treatment, for example, a hot air dryer, a papermaking machine, a dry pulp machine, etc. can be used.

[0085] The mixture after the heat treatment may be washed. This washing may be performed with water or the like. By this washing, the unreacted remaining urea and the like can be removed.

[0086] (slurry) If necessary, the microfiber cellulose is dispersed in an aqueous medium to form a dispersion (slurry). The aqueous medium is particularly preferably entirely water, but an aqueous medium containing other liquids that are partially compatible with water can also be used. As the other liquid, lower alcohols having 3 or less carbon atoms can be used.

[0087] The solid content of the slurry is preferably 0.1 to 10.0% by mass, more preferably 0.5 to 5.0% by mass. If the solid content is less than 0.1% by mass, excessive energy may be required for dehydration or drying. On the other hand, if the solid content is more than 10.0% by mass, the fluidity of the slurry itself may decrease, and when a dispersant is used, the slurry may not be mixed uniformly.

[0088] (Acid-modified resin) As described above, in the acid-modified resin, the acid groups are ionic-bonded to some or all of the carbamate groups, and this ionic bond improves the reinforcing effect of the resin.

[0089] Examples of the acid-modified resin include acid-modified polyolefin resin, acid-modified epoxy resin, and acid-modified styrene-based elastomer resin. However, it is preferable to use an acid-modified polyolefin resin. The acid-modified polyolefin resin is a copolymer of an unsaturated carboxylic acid component and a polyolefin component.

[0090] As the polyolefin component, for example, one or more types selected from polymers of alkenes such as ethylene, propylene, butadiene, isoprene, etc., can be used. However, it is preferable to use a polypropylene resin, which is a polymer of propylene.

[0091] As the unsaturated carboxylic acid component, for example, one or more selected from maleic anhydrides, phthalic anhydrides, itaconic anhydrides, citraconic anhydrides, citric anhydrides, etc. can be used. However, it is preferable to use maleic anhydrides. In other words, it is preferable to use maleic anhydride-modified polypropylene resin.

[0092] The amount of the acid-modified resin is preferably 0.1 to 1,000 parts by mass, more preferably 1 to 500 parts by mass, and particularly preferably 10 to 200 parts by mass, relative to 100 parts by mass of the microfiber cellulose. In particular, when the acid-modified resin is a maleic anhydride-modified polypropylene resin, the amount is preferably 1 to 200 parts by mass, more preferably 10 to 100 parts by mass. If the amount of the acid-modified resin is less than 0.1 parts by mass, the strength is not sufficiently improved. On the other hand, if the amount is more than 1,000 parts by mass, the strength tends to decrease due to the excessive amount.

[0093] The weight average molecular weight of the maleic anhydride modified polypropylene is, for example, 1,000 to 100,000, and preferably 3,000 to 50,000.

[0094] The acid value of the maleic anhydride modified polypropylene is preferably 0.5 mgKOH / g or more and 100 mgKOH / g or less, and more preferably 1 mgKOH / g or more and 50 mgKOH / g or less.

[0095] Furthermore, the MFR (melt flow rate) of the acid-modified resin is preferably 2000 g / 10 min (190° C. / 2.16 kg) or less, more preferably 1500 g / 10 min or less, and particularly preferably 500 g / 10 min or less. If the MFR exceeds 2000 g / 10 min, the dispersibility of the cellulose fibers may decrease.

[0096] The acid value is measured in accordance with JIS-K2501 by titration with potassium hydroxide, and the MFR is measured in accordance with JIS-K7210 by placing a load of 2.16 kg at 190°C and measuring the weight of the sample that flows out in 10 minutes.

[0097] (Dispersant) The cellulose raw material or microfiber cellulose is more preferably mixed with a dispersant, which is preferably an aromatic compound having an amine group and / or a hydroxyl group, or an aliphatic compound having an amine group and / or a hydroxyl group.

[0098] Examples of compounds having an amine group and / or a hydroxyl group in an aromatic group include anilines, toluidines, trimethylanilines, anisidines, tyramines, histamines, tryptamines, phenols, dibutylhydroxytoluenes, bisphenol A, cresols, eugenols, gallic acids, guaiacols, picric acids, phenolphthaleins, serotonins, dopamines, adrenalines, noradrenalines, thymols, tyrosines, salicylic acids, methyl salicylates, a Examples of such alcohols include varnish alcohols, salicylic alcohols, sinapyl alcohols, diphenidols, diphenylmethanols, cinnamyl alcohols, scopolamines, tryptophols, vanillyl alcohols, 3-phenyl-1-propanols, phenethyl alcohols, phenoxyethanols, veratryl alcohols, benzyl alcohols, benzoins, mandelic acids, mandelonitriles, benzoic acids, phthalic acids, isophthalic acids, terephthalic acids, mellitic acids, and cinnamic acids.

[0099] Examples of compounds having an amine group and / or a hydroxyl group in an aliphatic group include capryl alcohols, 2-ethylhexanols, pelargonic alcohols, capric alcohols, undecyl alcohols, lauryl alcohols, tridecyl alcohols, myristyl alcohols, pentadecyl alcohols, cetanols, stearyl alcohols, elaidyl alcohols, oleyl alcohols, linoleyl alcohols, methylamines, dimethylamines, trimethylamines, ethylamines, diethylamines, and ethylenediamines. , triethanolamines, N,N-diisopropylethylamines, tetramethylethylenediamines, hexamethylenediamines, spermidines, spermines, amantadines, formic acids, acetic acids, propionic acids, butyric acids, valeric acids, caproic acids, enanthic acids, caprylic acids, pelargonic acids, capric acids, lauric acids, myristic acids, palmitic acids, margaric acids, stearic acids, oleic acids, linoleic acids, linolenic acids, arachidonic acids, eicosapentaenoic acids, docosahexaenoic acids, and sorbic acids.

[0100] The above dispersants inhibit hydrogen bonding between cellulose fibers. Therefore, the microfibrous cellulose is reliably dispersed in the resin when the microfibrous cellulose and the resin are kneaded. The above dispersants also have the role of improving the compatibility of the microfibrous cellulose and the resin. In this respect, the dispersibility of the microfibrous cellulose in the resin is improved.

[0101] It is possible to add a separate compatibilizer (chemical) when kneading the fibrous cellulose and resin, but mixing the fibrous cellulose and dispersing agent (chemical) in advance rather than adding the chemical at this stage will ensure that the chemical sticks to the fibrous cellulose evenly, and will be more effective in improving compatibility with the resin.

[0102] Also, for example, polypropylene has a melting point of 160°C, so the kneading of fibrous cellulose and resin is carried out at about 180°C. However, if a dispersant (liquid) is added in this state, it dries out in an instant. Therefore, there is a method in which a master batch (composite resin with a high concentration of microfiber cellulose) is produced using a resin with a low melting point, and then the concentration is reduced with a normal resin. However, resins with low melting points generally have low strength. Therefore, this method may reduce the strength of the composite resin.

[0103] The amount of the dispersant mixed is preferably 0.1 to 1,000 parts by mass, more preferably 1 to 500 parts by mass, and particularly preferably 10 to 200 parts by mass, relative to 100 parts by mass of the microfiber cellulose. If the amount of the dispersant mixed is less than 0.1 parts by mass, the improvement in resin strength may be considered insufficient. On the other hand, if the amount mixed is more than 1,000 parts by mass, the resin strength tends to decrease due to excessive use.

[0104] In this respect, the acid-modified resin described above is intended to improve compatibility by ionic bonding between the acid group and the carbamate group of the microfiber cellulose, thereby enhancing the reinforcing effect, and is considered to be compatible with the resin due to its large molecular weight, thereby contributing to improving strength. On the other hand, the dispersant described above is intended to intervene between the hydroxyl groups of the microfiber cellulose to prevent aggregation, thereby improving dispersibility in the resin, and since its molecular weight is smaller than that of the acid-modified resin, it can enter the narrow space between the microfiber cellulose that the acid-modified resin cannot enter, thereby improving dispersibility and improving strength. From the above viewpoint, the molecular weight of the acid-modified resin is preferably 2 to 2,000 times, preferably 5 to 1,000 times, the molecular weight of the dispersant.

[0105] To explain this in more detail, the resin powder physically intervenes between the microfiber cellulose particles, thereby inhibiting hydrogen bonding, and thereby improving the dispersibility of the microfiber cellulose. In contrast, the acid-modified resin ionically bonds the acid group with the carbamate group of the microfiber cellulose, thereby improving compatibility, and thereby enhancing the reinforcing effect. In this respect, the dispersant inhibits hydrogen bonding between the microfiber cellulose particles, but since the resin powder is on the micro-order, it physically intervenes and suppresses hydrogen bonding. Therefore, although the dispersibility is lower than that of the dispersant, the resin powder itself melts and becomes a matrix, so it does not contribute to a decrease in physical properties. On the other hand, the dispersant is at the molecular level and is extremely small, so it covers the microfiber cellulose, inhibiting hydrogen bonding, and is highly effective in improving the dispersibility of the microfiber cellulose. However, it may remain in the resin and affect the decrease in physical properties.

[0106] (Manufacturing method) The mixture of fibrous cellulose, acid-modified resin, dispersant, etc. can be dried and pulverized to a powder before kneading with the resin. In this form, there is no need to dry the fibrous cellulose when kneading with the resin, and thermal efficiency is good. In addition, when a dispersant is mixed into the mixture, there is a low risk that the fibrous cellulose (microfiber cellulose) will not be redispersed even if the mixture is dried.

[0107] If necessary, the mixture may be dehydrated prior to drying to obtain a dehydrated product, which may be carried out using one or more dehydration devices selected from the group consisting of a belt press, a screw press, a filter press, a twin roll, a twin wire former, a valveless filter, a center disk filter, a membrane treatment device, and a centrifuge.

[0108] The mixture can be dried by using one or more selected from, for example, rotary kiln drying, disc drying, air flow drying, media flow drying, spray drying, drum drying, screw conveyor drying, paddle drying, uniaxial kneading drying, multiaxial kneading drying, vacuum drying, stirring drying, and the like.

[0109] The dried mixture (dried product) is pulverized to obtain a powder. The dried product can be pulverized using one or more of a bead mill, a kneader, a disperser, a twist mill, a cut mill, a hammer mill, etc.

[0110] The average particle size of the powdery material is preferably 1 to 10,000 μm, more preferably 10 to 5,000 μm, and particularly preferably 100 to 1,000 μm. If the average particle size of the powdery material exceeds 10,000 μm, it may be poor in kneadability with resin. On the other hand, it is not economical to reduce the average particle size of the powdery material to less than 1 μm because a large amount of energy is required.

[0111] The average particle size of the powdery material can be controlled by controlling the degree of pulverization, as well as by classification using a classifying device such as a filter or a cyclone.

[0112] The bulk density of the mixture (powder material) is preferably 0.03 to 1.0, more preferably 0.04 to 0.9, and particularly preferably 0.05 to 0.8. A bulk density exceeding 1.0 means that the hydrogen bonds between the fibrous cellulose are stronger, and it is not easy to disperse the cellulose in the resin. On the other hand, a bulk density below 0.03 is disadvantageous in terms of transportation costs.

[0113] The bulk density is a value measured in accordance with JIS K7365.

[0114] The moisture content of the mixture (powder material) is preferably 50% or less, more preferably 30% or less, and particularly preferably 10% or less. If the moisture content exceeds 50%, the energy required for kneading with the resin becomes enormous, which is not economical.

[0115] The moisture content was calculated using the following formula by holding the sample at 105°C for 6 hours or more in a constant temperature dryer and measuring the mass after drying at the point where no change in mass was observed. Fiber moisture content (%) = [(mass before drying - mass after drying) ÷ mass before drying] x 100

[0116] The dehydrated and dried microfiber cellulose may contain a resin. If a resin is contained, the hydrogen bonds between the dehydrated and dried microfiber cellulose are inhibited, and the dispersibility in the resin during kneading can be improved.

[0117] The form of the resin contained in the dehydrated and dried microfiber cellulose may be, for example, powder, pellet, sheet, etc. However, powder (powdered resin) is preferred.

[0118] When the resin powder is in powder form, the average particle size of the resin powder contained in the dehydrated and dried microfiber cellulose is preferably 1 to 10,000 μm, more preferably 10 to 5,000 μm, and particularly preferably 100 to 1,000 μm. If the average particle size exceeds 10,000 μm, the particles may be too large to enter the kneading device. On the other hand, if the average particle size is less than 1 μm, the particles may be too fine to inhibit hydrogen bonding between the microfiber cellulose. The resin, such as the powdered resin, used here may be the same or different from the resin (resin as the main raw material) to be kneaded with the microfiber cellulose, but it is preferable that the resin is the same type.

[0119] Resin powder with an average particle size of 1 to 10,000 μm is preferably mixed in an aqueous dispersion state before dehydration and drying. By mixing in an aqueous dispersion state, the resin powder can be uniformly dispersed among the microfiber cellulose, and the microfiber cellulose can be uniformly dispersed in the composite resin after kneading, thereby further improving the strength properties.

[0120] The powdery material (resin reinforcing material) obtained as described above is kneaded with resin to obtain a fibrous cellulose composite resin. This kneading can be performed, for example, by mixing the powdery material with a pellet-like resin, or by melting the resin first and adding the powdery material to the melt. Acid-modified resins, dispersants, etc. can also be added at this stage.

[0121] For the kneading treatment, for example, one or more of a single-shaft or multi-shaft kneader having two or more shafts, a mixing roll, a kneader, a roll mill, a Banbury mixer, a screw press, a disperser, etc. can be selected and used. Among them, it is preferable to use a multi-shaft kneader having two or more shafts. Two or more multi-shaft kneaders having two or more shafts may be used in parallel or in series.

[0122] The kneading temperature is equal to or higher than the glass transition point of the resin, and differs depending on the type of resin, but is preferably 80 to 280°C, more preferably 90 to 260°C, and particularly preferably 100 to 240°C.

[0123] As the resin, at least one of a thermoplastic resin and a thermosetting resin can be used.

[0124] As the thermoplastic resin, for example, one or more selected from polyolefins such as polypropylene (PP) and polyethylene (PE), polyester resins such as aliphatic polyester resins and aromatic polyester resins, polyacrylic resins such as polystyrene, methacrylate and acrylate, polyamide resins, polycarbonate resins, polyacetal resins, etc. can be used.

[0125] However, it is preferable to use at least one of polyolefin and polyester resin. As the polyolefin, it is preferable to use polypropylene. As the polyester resin, examples of the aliphatic polyester resin include polylactic acid and polycaprolactone, and examples of the aromatic polyester resin include polyethylene terephthalate, but it is preferable to use a biodegradable polyester resin (also simply called "biodegradable resin").

[0126] As the biodegradable resin, for example, one or more types may be selected from hydroxycarboxylic acid-based aliphatic polyesters, caprolactone-based aliphatic polyesters, dibasic acid polyesters, and the like and used.

[0127] As the hydroxycarboxylic acid-based aliphatic polyester, one or more selected from homopolymers of hydroxycarboxylic acids such as lactic acid, malic acid, glucose acid, 3-hydroxybutyric acid, etc., and copolymers using at least one of these hydroxycarboxylic acids, etc. However, it is preferable to use polylactic acid, copolymers of lactic acid and the above hydroxycarboxylic acids other than lactic acid, polycaprolactone, and copolymers of at least one of the above hydroxycarboxylic acids and caprolactone, and it is particularly preferable to use polylactic acid.

[0128] As the lactic acid, for example, L-lactic acid, D-lactic acid, etc. can be used, and these lactic acids may be used alone or in combination of two or more kinds.

[0129] As the caprolactone-based aliphatic polyester, for example, one or more types may be selected from homopolymers of polycaprolactone and copolymers of polycaprolactone or the like with the above-mentioned hydroxycarboxylic acids and the like.

[0130] As the dibasic acid polyester, for example, one or more types may be selected from polybutylene succinate, polyethylene succinate, polybutylene adipate, and the like and used.

[0131] The biodegradable resin may be used alone or in combination of two or more kinds.

[0132] Examples of the thermosetting resin that can be used include phenol resins, urea resins, melamine resins, furan resins, unsaturated polyesters, diallyl phthalate resins, vinyl ester resins, epoxy resins, urethane resins, silicone resins, thermosetting polyimide resins, etc. These resins can be used alone or in combination of two or more.

[0133] The resin may contain an inorganic filler, preferably in a proportion that does not interfere with thermal recycling.

[0134] Examples of inorganic fillers include simple substances, oxides, hydroxides, carbonates, sulfates, silicates, and sulfites of metal elements in Groups I to VIII of the periodic table, such as Fe, Na, K, Cu, Mg, Ca, Zn, Ba, Al, Ti, and silicon, as well as various clay minerals composed of these compounds.

[0135] Specific examples include barium sulfate, calcium sulfate, magnesium sulfate, sodium sulfate, calcium sulfite, zinc oxide, silica, heavy calcium carbonate, light calcium carbonate, aluminum borate, alumina, iron oxide, calcium titanate, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, sodium hydroxide, magnesium carbonate, calcium silicate, clay wollastonite, glass beads, glass powder, silica sand, silica stone, quartz powder, diatomaceous earth, white carbon, glass fiber, etc. A plurality of these inorganic fillers may be contained. Also, it may be one contained in waste paper pulp.

[0136] The blending ratio of fibrous cellulose and resin is preferably 1 part by mass or more of fibrous cellulose and 99 parts by mass or less of resin, more preferably 2 parts by mass or more of fibrous cellulose and 98 parts by mass or less of resin, particularly preferably 3 parts by mass or more of fibrous cellulose and 97 parts by mass or less of resin. Also, preferably 50 parts by mass or less of fibrous cellulose and 50 parts by mass or more of resin, more preferably 40 parts by mass or less of fibrous cellulose and 60 parts by mass or more of resin, particularly preferably 30 parts by mass or less of fibrous cellulose and 70 parts by mass or more of resin. In particular, when the fibrous cellulose is 10 to 50 parts by mass, the strength of the resin composition, particularly the bending strength and tensile modulus, can be significantly improved.

[0137] The content ratio of the fibrous cellulose and the resin in the final resin composition is usually the same as the above-mentioned blending ratio of the fibrous cellulose and the resin.

[0138] Solubility parameters (cal / cm) of microfiber cellulose and resin 3 ) 1 / 2 (SP value), that is, the SP of microfiber cellulose MFC Value, resin SP POL value, the difference in SP value = SP MFC Value − SP POL The difference in SP value is preferably 10 to 0.1, more preferably 8 to 0.5, and particularly preferably 5 to 1. If the difference in SP value exceeds 10, the microfiber cellulose may not disperse in the resin, and the reinforcing effect may not be obtained. On the other hand, if the difference in SP value is less than 0.1, the microfiber cellulose will dissolve in the resin, will not function as a filler, and the reinforcing effect will not be obtained. In this regard, the SP of the resin (solvent) POL Value and SP of microfiber cellulose (solute) MFC The smaller the difference in the values, the greater the reinforcing effect.

[0139] The solubility parameter (cal / cm 3 ) 1 / 2 The SP value is a measure of the intermolecular force acting between a solvent and a solute, and the closer the SP values ​​of the solvent and solute are, the greater the solubility.

[0140] (Molding process) The kneaded product of the fibrous cellulose and the resin can be molded into a desired shape after, if necessary, re-kneading, etc. The size, thickness, shape, etc. of the molded product are not particularly limited, and can be, for example, a sheet, pellet, powder, fiber, etc.

[0141] The temperature during the molding process is equal to or higher than the glass transition point of the resin, and differs depending on the type of resin, but is, for example, 90 to 260°C, and preferably 100 to 240°C.

[0142] The kneaded material can be molded by, for example, mold molding, injection molding, extrusion molding, hollow molding, foam molding, etc. The kneaded material can also be spun into fibers and mixed with the above-mentioned plant materials to form a mat or board. The mixed fibers can be simultaneously deposited by air laying, for example.

[0143] As the apparatus for molding the kneaded product, for example, one or more types may be selected from an injection molding machine, a blow molding machine, a hollow molding machine, a blow molding machine, a compression molding machine, an extrusion molding machine, a vacuum molding machine, a pressure molding machine, etc., and may be used.

[0144] The above molding can be carried out following kneading, or the kneaded mixture can be cooled once and then chipped using a crusher or the like, and the chips can be fed into a molding machine such as an extrusion molding machine or an injection molding machine. Of course, molding is not an essential requirement of the present invention.

[0145] The fibrous cellulose composite resin obtained as described above has a standard deviation of the flexural modulus of preferably 30 MPa or less, more preferably 29 MPa or less, and particularly preferably 28 MPa or less. If the standard deviation exceeds 30 MPa, when the resin is used as a material, it may be necessary to take measures such as increasing the thickness of the material more than necessary or using a reinforcing material in order to maintain the minimum required physical properties while taking into account the variations, which may result in an increase in costs.

[0146] In the present embodiment, the flexural modulus is a value measured in accordance with JIS K 7171.

[0147] (Other compositions) The fibrous cellulose may contain cellulose nanofibers together with microfiber cellulose. Cellulose nanofibers are fine fibers like microfiber cellulose, and play a role in complementing microfiber cellulose in improving the strength of resin. However, if possible, it is preferable to use only microfiber cellulose as fine fibers without including cellulose nanofibers. The average fiber diameter of the cellulose nanofibers (average fiber width; average diameter of a single fiber) is preferably 4 to 100 nm, more preferably 10 to 80 nm.

[0148] The fibrous cellulose may also contain pulp. Pulp plays a role in significantly improving the dewaterability of the cellulose fiber slurry. However, as with the cellulose nanofiber, it is most preferable that no pulp is added, that is, that the content is 0 mass%.

[0149] The resin composition can contain, or may contain, in addition to fine fibers and pulp, fibers derived from plant materials obtained from various plants such as kenaf, jute, Manila hemp, sisal, gampi, mitsumata, paper mulberry, banana, pineapple, coconut, corn, sugarcane, bagasse, palm, papyrus, reed, esparto, sabai grass, wheat, rice, bamboo, various coniferous trees (such as cedar and cypress), broad-leaved trees, and cotton.

[0150] For example, one or more of antistatic agents, flame retardants, antibacterial agents, colorants, radical scavengers, foaming agents, etc. may be added to the resin composition within a range that does not impair the effects of the present invention. These raw materials may be added to a dispersion of fibrous cellulose, added when kneading fibrous cellulose and resin, added to a kneaded product thereof, or added by other methods. However, from the viewpoint of production efficiency, it is preferable to add them when kneading fibrous cellulose and resin.

[0151] The resin composition may contain an ethylene-α-olefin copolymer elastomer or a styrene-butadiene block copolymer as a rubber component. Examples of α-olefins include butene, isobutene, pentene, hexene, methyl-pentene, octene, decene, and dodecene.

[0152] (Definition, measurement method, etc.) (Average fiber diameter) The method for measuring the average fiber diameter of fine fibers (microfiber cellulose and cellulose nanofiber) is as follows. First, 100 ml of an aqueous dispersion of fine fibers with a solid content concentration of 0.01 to 0.1% by mass is filtered through a Teflon (registered trademark) membrane filter, and the solvent is replaced once with 100 ml of ethanol and three times with 20 ml of t-butanol. Next, the sample is freeze-dried and osmium-coated to obtain a sample. This sample is observed using an electron microscope SEM image at a magnification of 3,000 to 30,000 times depending on the width of the fibers that constitute it. Specifically, two diagonal lines are drawn on the observed image, and three straight lines passing through the intersections of the diagonal lines are arbitrarily drawn. Furthermore, the widths of a total of 100 fibers that intersect with these three straight lines are visually measured. The median diameter of the measured values ​​is then taken as the average fiber diameter.

[0153] (Aspect Ratio) The aspect ratio is the average fiber length divided by the average fiber width. The larger the aspect ratio, the more points at which snagging occurs, and therefore the greater the reinforcing effect. However, on the other hand, the more snagging occurs, and this is thought to reduce the ductility of the resin.

[0154] (Water retention) The water retention is a value measured in accordance with JAPAN TAPPI No. 26 (2000).

[0155] (Fiber Analysis) The fine rate, fibrillation rate, average fiber length, etc. were measured using a fiber analyzer "FS5" manufactured by Valmet.

[0156] (Crystallization degree) The crystallinity is a value measured in accordance with JIS K 0131 (1996).

[0157] (viscosity) The pulp viscosity is a value measured in accordance with TAPPI T 230.

[0158] (B type viscosity) The B-type viscosity of the dispersion (solid content 1%) is a value measured in accordance with JIS-Z8803 (2011) "Method of measuring viscosity of liquids." B-type viscosity is the resistance torque when the dispersion is stirred, and the higher the viscosity, the more energy is required for stirring.

[0159] (Freeness) The freeness is a value measured in accordance with JIS P8121-2 (2012). EXAMPLES

[0160] Next, an embodiment of the present invention will be described. Softwood kraft pulp with a moisture content of 10% or less, an aqueous urea solution with a solid content concentration of 10%, and various pH adjusting solutions were mixed in the ratios shown in Table 1 (mass ratio converted to solid content. The amount of pH adjusting solution is not shown. Since urea is a weak base, the amount of pH adjusting solution is small (about 0.02 to 0.2 g / g of urea).) This mixture was dried at 105°C to obtain a dried body. This dried body was heat-treated at 140°C (reaction temperature) for 3 hours (reaction time) to obtain carbamate-modified pulp. The carbamate-modified pulp thus obtained was diluted and stirred with distilled water, and dehydrated and washed twice. The washed carbamate-modified pulp was beaten with a Niagara beater for 4 hours to obtain carbamate-modified microfibrous cellulose (fibrous cellulose) with the desired fine ratio. The fine ratio and average fiber length of this carbamate-modified microfibrous cellulose are shown in Table 1.

[0161] Next, 27.5 g of maleic anhydride-modified polypropylene and 17.5 g of polypropylene powder were added to 2750 g of the carbamate-modified microfiber cellulose aqueous dispersion having a solid content concentration of 2% by mass, and the mixture was dried by heating at 105°C to obtain a carbamate-modified microfiber cellulose-containing material. The water content of this carbamate-modified microfiber cellulose-containing material was less than 20%. The carbamate-modified microfiber-containing material was kneaded in a twin-screw kneader under conditions of 180°C and 200 rpm to obtain a carbamate-modified microfiber cellulose composite resin having a fiber loading rate of 55%.

[0162] Furthermore, polypropylene pellets were added to this carbamate-modified microfiber cellulose composite resin so that the ratio of carbamate-modified microfiber to other components was 10:90, and the mixture was kneaded in a twin-screw kneader at 180°C and 200 rpm to obtain a carbamate-modified microfiber cellulose composite resin with a fiber loading rate of 10%. The carbamate-modified microfiber cellulose composite resin with a fiber loading rate of 10% was cut into a cylindrical shape with a diameter of 2 mm and a length of 2 mm using a pelleter, and injection molded into a rectangular parallelepiped test piece (length 59 mm, width 9.6 mm, thickness 3.8 mm) at 180°C. The flexural modulus and flexural modulus deviation of the molded product are shown in Table 1.

[0163] In the bending test, the bending modulus was first examined in accordance with JIS K7171:2008. In the table, the bending modulus (1.38 GPa) of the resin itself (blank) is taken as 1, and cases where the bending modulus (magnification) of the composite resin is 1.3 times or more are indicated as "○", and cases where it is less than 1.3 times are indicated as "×". The variation in bending modulus was evaluated using the standard deviation σ of the four test specimens (composite resin) measured. When σ was less than 30, it was indicated as "○", and when it was 30 or more, it was indicated as "×".

[0164] [Table 1]

[0165] (Consideration) From the table, it can be seen that even if the fine ratio is less than 30%, the flexural modulus improves, but the flexural modulus fluctuates greatly. Therefore, from the viewpoint of the reinforcing effect of the resin, especially the prevention of breakage of the resin, it is preferable that the fine ratio is 30% or more. [Industrial Applicability]

[0166] The present invention can be used as fibrous cellulose, fibrous cellulose composite resin, and a method for producing fibrous cellulose. For example, the fibrous cellulose composite resin can be used for interior materials, exterior materials, structural materials, etc. of transportation equipment such as automobiles, trains, ships, and airplanes; housings, structural materials, internal parts, etc. of electrical appliances such as personal computers, televisions, telephones, and watches; housings, structural materials, internal parts, etc. of mobile communication equipment such as mobile phones; housings, structural materials, internal parts, etc. of portable music playback equipment, video playback equipment, printing equipment, copying equipment, sports equipment, office equipment, toys, sports equipment, etc.; interior materials, exterior materials, structural materials, etc. of buildings, furniture, etc.; office equipment such as stationery; and other containers such as packaging bodies and trays, protective materials, partition members, etc.

Claims

1. The average fiber width is 0.1 μm or more, and some or all of the hydroxyl groups are "-CO-NH 2 " group, The substitution rate of the carbamate group is 1.0 mmol / g or more, The fine ratio is 30% or more, The average fiber length is 0.15 to 0.95 mm. Fibrous cellulose characterized by:

2. The fine ratio is 40% or more.

2. The fibrous cellulose of claim 1.

3. The fine ratio of the raw cellulose material is 1% or more. The fibrous cellulose according to claim 1 or 2.

4. Contains fibrous cellulose and resin, The fibrous cellulose is The average fiber width is 0.1 μm or more, and some or all of the hydroxyl groups are "-CO-NH 2 " group, The substitution rate of the carbamate group is 1.0 mmol / g or more, The fine ratio is 30% or more, The average fiber length is 0.15 to 0.95 mm. A fibrous cellulose composite resin characterized by:

5. The standard deviation of the flexural modulus measured in accordance with JIS K 7171 is 30 MPa or less. The fibrous cellulose composite resin according to claim 4.

6. At least one of a cellulose raw material and urea and a derivative of urea is heat-treated to convert a part or all of the hydroxyl groups of the cellulose raw material into "-CO-NH 2 " group; and and defibrating the cellulose raw material to an average fiber width of 0.1 μm or more. The heat treatment is carried out so that the substitution rate of the carbamate group is 1.0 mmol / g or more; The defibration is carried out until the fineness ratio reaches 30% or more. The average fiber length is 0.15 to 0.95 mm.

5. A method for producing fibrous cellulose comprising the steps of:

Citation Information

Patent Citations

  • Cellulose nanofiber production device and method for producing cellulose nanofiber

    JP2018048235A

  • Cellulose nanofiber production device and method for producing cellulose nanofiber

    JP2018048237A

  • Apparatus and method for producing cellulose nanofiber

    JP2018090738A

  • Apparatus for producing cellulose nanofiber and method for producing cellulose nanofiber

    JP2018100474A

  • Fine cellulose fiber, manufacturing method therefor, slurry, and composite

    JP2019001876A

Cited By

  • Fibrous cellulose, fibrous cellulose composite resin, and method for producing fibrous cellulose

    JP2025003524A

  • Fibrous cellulose composite resin and method for producing fibrous cellulose

    JP7864800B2